Studies on the Proximate Composition, Quality and Heavy Metal Concentration of two Sun-Dried Marine Fish (Sun-Dried Silver Pomfret and Sun-Dried Perch) of Cox’s Bazar District of Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
This research was conducted on the proximate composition, quality aspect and heavy metal concentration of sun-dried Silver Pomfret (Stromateus cinereus) and sun-dried Perch (Lates calcarifer) which were collected from local market of Cox‟s Bazar town. These sun-dried marine fishes were collected from the stock after first drying procedure. Organoleptically most of these sun-dried fishes were in „excellent‟ grade some were in „Good‟ grade. Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N content (%) of sun-dried Silver Pomfret (Stromateus cinereus) was 32.25±1.50, 7.75±0.20, 39.59±0.34, 15.75±0.39, 85.68±1.60 and 8.41±0.37 respectively. Whereas in sun-dried Perch (Lates calcarifer) the content (%) of Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N was 40.31±2.13, 5.03±0.55, 26.74±0.47, 11.50±0.26, 46.97±1.00 and 8.21±0.12 respectively. Heavy metal concentration i.e. Cd, Cr, Pb, Cu and Zn concentration (ppm) in sun-dried Silver Pomfret (Stromateus cinereus) was 0.68, 5.85, 8.43, 1.15, 24.93 ppm. Whereas heavy metal concentration (ppm) in sun-dried Perch (Lates calcarifer) was Cd 0.65 ppm, Cr 5.6 ppm, Pb 6.28 ppm, Cu 1.04 ppm, Zn 23.8 ppm.J. Environ. Sci. & Natural Resources, 10(1): 25-32 2017